THE ADJUSTED MARKET POWER, COMPETITION, AND PERFORMANCE: ISLAMIC VS CONVENTIONAL BANKS - Mudeer Ahmed Khattak; Mohsin Ali; Noureen A. Khan; Fawad Ahmad (Journal of Islamic Monetary Economics and Finance, 2022)
This study explores the relationship between competition and performance in a dual-banking setting. More specifically, we compare whether using the Traditional Lerner index (TLI) the efficiency-adjusted Lerner index (EALI) would yield different conclusions. We take data from 2008 to 2020 and take Malaysia as a case study. Considering the nature of the dataset and the variables within, we employ the system Generalized Method of Moments. Our findings reveal contradictory results when market power is measured differently. Based on the overall sample, the models using the adjusted market power is supportive of the ‘competition-stability view’ while the models with TLI report evidence in favor of the ‘competition-fragility view.’ The Islamic banks' results support the ‘competition-fragility view’ when competition is measured with the efficiency-adjusted Lerner index (EALI) and the ‘competition-stability view’ when measured with the TLI. These findings are robust to different econometric estimators and carry important policy implications.